Firm Size and the Nature of Innovation within Industries: The Case of Process and Product R&D - Cohen, Wesley M.; Klepper, Steven (The Review of Economics and Statistics, 1996)
Wesley M. Cohen, Steven Klepper, Firm Size and the Nature of Innovation within Industries: The Case of Process and Product R&D, The Review of Economics and Statistics, Vol. 78, No. 2 (May, 1996), pp. 232-243